Feasibility Analysis of Melvin Eating House Business Mackerel Fish Batagor Siomay (Agrikan Jurnal Agribisnis Perikanan, 2024)
Batagor and Siomay are typical West Javanese foods that are known to almost all Indonesian people, especially in South Kalimantan. One of the visionaries who introduced batagor and siomay in Banjarbaru, South Kalimantan, was the Melvin restaurant which is located on Jalan Ahmad Yani km 34. The methods used were observation, interviews and documentation within two months. The data analysis methods used are cost, income, profit analysis and business feasibility analysis. This research aims to determine the business feasibility of the Melvin Batagor restaurant, Tenggiri fish dumplings. From the results of the research carried out, it was found that the annual profit from Melvin's Batagor Siomay Restaurant was IDR 143,058,500.00. Business feasibility (R/C) was 1.36 because it was greater than 1, so this restaurant business was feasible to develop. The BEP for Melvin's batagor siomay production is 15,877.66 pices, while the BEP price is IDR 22,052.30. Because the selling price and quantity of batagor and dumplings produced are above the break-even point, Melvin's batagor siomay restaurant business can be said to be profitable.
Keywords: Batagor; Siomay; Business Analys